Feasibility Assessment of Wind Energy-Driven Automatic Irrigation System for Jos Plateau - Daniel, Samson; Aliyu, Hassan; Mamman, Buhari; Musa, Yarima Sa’id; Nazif, D. M. (Asian Journal of Science, Technology, Engineering, and Art, 2025)
Nigeria's over-reliance on rainfall agriculture is reducing crop yield and keeping farm output below demand, despite irrigation farming providing insurance for rain-fed agriculture even during rainy seasons. The location of study is Jos, Plateau State, where year-round wind speeds of 3 to 9.37 m/s make providing electricity for irrigation water pumping feasible, and the nature of the terrain which enables the pump hydro storage technology. This study explores the feasibility of a wind-powered pump hydro storage scheme for smart irrigation systems, generating electricity to pump water and charge a battery bank. The farm uses a battery storage for irrigation control, powered by a microcontroller. The system monitors farm parameters using soil moisture and water level sensors. Raw wind data was upgraded from 10m to 50m hub height for improved power generation. The S3-1000-B8 wind turbine produces enough energy to pump a minimum of 8.7 m3 and a maximum of 176 m3 of water every week. Polynomial regression was used to calculate the wind power produced by this turbine, making it appropriate for this task. The 180 m3 of irrigation water needed per week to irrigate 10,000 m2 of agriculture was provided by 20 (S3-1000-B8) wind turbines. 720m3 of stored water is required for a month of safe irrigation. Based on wind potential, a single wind turbine can pump 234.864m3 of water and provide an average of 16kWh of energy every month. Consequently, the wind farm produces about 336 kWh and pumps 4,932 m3 in total.